The Role of Emotional Intelligence in Ensuring the Effectiveness of Professional Communication Processes - Arusiak Amarian (Emerging Frontiers Library for The American Journal of Management and Economics Innovations, 2025)
This article examines the critical role that emotional intelligence (EI) plays in enhancing professional communication. It outlines how EI facilitates effective interpersonal exchanges in the workplace by enabling individuals to recognize, understand, and manage emotions—the key to clear messaging, empathetic listening, and conflict resolution. The paper reviews foundational theoretical models (such as the Mayer-Salovey ability model and Goleman’s competency framework) and illustrates their relevance to leadership communication, conflict management, and team collaboration. Finally, it discusses evidence-based strategies—ranging from targeted training and coaching to practical skill-building exercises—that organizations can implement to foster an emotionally intelligent communication climate, thereby boosting productivity, engagement, and overall organizational performance.